Beginning JavaScript - Wilton, Paul, 1969- (Programmer to programmer., 2010)
The perennial bestseller returns with new details for using the latest tools and techniques available with JavaScript. JavaScript is the definitive language for making the Web a dynamic, rich, interactive medium. This guide to JavaScript builds on the success of previous editions and introduces you to many new advances in JavaScript development. The reorganization of the chapters helps streamline your learning process while new examples provide you with updated JavaScript programming techniques. You'll get all-new coverage of Ajax for remote scripting, JavaScript frameworks, JavaScript and XML.